Beat the heat. - Ross, P.E (IEEE spectrum)
One of the most burning issues confronting designers is how to keep microprocessors cool enough to operate. Possibilities on the horizon include tiny, self-contained evaporative cooling systems and even devices that capture the heat and turn it directly into electricity.